2021
DOI: 10.1038/s41396-020-00866-x
|View full text |Cite
|
Sign up to set email alerts
|

Functional mutants of Azospirillum brasilense elicit beneficial physiological and metabolic responses in Zea mays contributing to increased host iron assimilation

Abstract: Iron (Fe), an essential element for plant growth, is abundant in soil but with low bioavailability. Thus, plants developed specialized mechanisms to sequester the element. Beneficial microbes have recently become a favored method to promote plant growth through increased uptake of essential micronutrients, like Fe, yet little is known of their mechanisms of action. Functional mutants of the epiphytic bacterium Azospirillum brasilense, a prolific grass-root colonizer, were used to examine mechanisms for promoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 78 publications
1
41
0
1
Order By: Relevance
“…What distinguishes ipdC from the other microbial inoculants examined in this study is its deficiency in producing auxin (indole-3-acetic acid), an important plant hormone. Our past studies showed that the HM053 mutant exhibited the highest level of auxin biosynthesis, being 2 times that of FP10 and 13 times that of ipdC [ 16 ]. We know that auxin biosynthesis in plants and Zn levels are strongly correlated [ 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…What distinguishes ipdC from the other microbial inoculants examined in this study is its deficiency in producing auxin (indole-3-acetic acid), an important plant hormone. Our past studies showed that the HM053 mutant exhibited the highest level of auxin biosynthesis, being 2 times that of FP10 and 13 times that of ipdC [ 16 ]. We know that auxin biosynthesis in plants and Zn levels are strongly correlated [ 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Images were only used qualitatively for determining spatial patterning of 65 Zn tracer in roots and shoots; hence no attempt was made to normalize image data. Comparative whole-plant radiographic images of 59 Fe 3+ and 59 Fe 2+ were also acquired from our prior work [ 16 ], but because of the faster decay rate of this radionuclide (t ½ 44.5 day), we only needed to expose these tissues for 16 h.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations